Answer:
The factors for the given polynomial is (x-y) and (a+1)
Therefore [tex]ax-y+x-ay=(x-y)(a+1)[/tex]
Step-by-step explanation:
Given polynomial expression is [tex]ax-y+x-ay[/tex]
To simplify the given polynomial:
[tex]ax-y+x-ay[/tex]
[tex]=ax+x-ay-y[/tex] ( Rewritting the above polynomial)
[tex]=(a+1)x-(a+1)y[/tex] (Taking the common terms )
[tex]=x(a+1)-y(a+1)[/tex](using commutative property )
[tex]=(x-y)(a+1)[/tex] (taking common factor )
Therefore [tex]ax-y+x-ay=(x-y)(a+1)[/tex]
Therefore the factors for the given polynomial is (x-y) and (a+1)